A semantic web technology based framework for educational-offer selection in higher education. (11th August 2009) - Kumar, Sandeep; Kumar, Kuldeep; Jain, Ankita
Semantic web technology can be applied to a wide range of application domains. Educational-offer selection is an area of the education domain, which can benefit greatly from the application of semantic web technology. The paper explores the educational-offer selection problem as an application of semantic web technology. It specifically deals with the problem of higher education admission. A semantic web-based model for educational-offer selection is presented. Further, Semantic Web Service (SWS) selection and composition models are shown to be applicable to the problem of educational-offer selection. A prototype system, implementing semantic web-based educational-offer selection, is presented.